PERAN PERKEMBANGAN TEKNOLOGI PADA TEKNIK INDUSTRI DALAM MENGHADAPI SOCIETY 5.0 - Muhammad Juanda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Rapid technological developments have brought us to the era of Society 5.0, an innovative concept that emerged from Industry 4.0. The goal of the Society 5.0 era is to build a human-centered individual, where change must be based on moral considerations. This concept is not only related to the manufacturing industry, but also includes the way anyone solves problems with the help of the integration of physical and virtual spaces. The concept of Society 5.0 is based on the problems facing Japan, such as decreasing population growth rates, decreasing productive age, and increasing the global greenhouse effect. This concept aims to improve society through various services, such as health, mobility, infrastructure technology and financial technology. With the many changes taking place, Indonesia will definitely face new challenges. Industrial Engineering, as a scientific discipline, plays an important role in meeting these challenges through the design, improvement, and installation of integrated systems of people, materials, information, equipment, and energy